Care nursing the spiritual dimension of the patient. Systematic review - María Teresa Pinedo Velázquez; Juan Carlos Jiménez Jiménez (Universidad de Alicante, 2017)
It is necessary to know the perception of nurses about the emotional attention given to patients at the spiritual dimension in patient care plan. The objective was to know the spiritual care offered by nurses in their daily work during a patient's hospital stay and detect possible associated factors that hinder the facing death. Material and Methods. The unit of analysis has been the primary original studies, electronic searches (Cuiden, Scielo, Pubmed) and manuals relevant of articles published in journals, bibliographies and reference lists of reviews and papers were made. Results and Conclusions. There are a number of factors that hinder the proper intervention of nursing professionals in specific situations of non-health: especially when the patient feels the urgent need to obtain information on their health status because it is admitted in a hospital in terminal situation, as when you communicate suddenly having a serious organic disorder in some body structure with some degree of limitation prevents regular physical activity.... as a result he feels emotions like anxiety, fear, depression, anger, dissatisfaction, etc which are emotions with high emotional and spiritual burden.